Mauqif al-JÄhiáº“ min al-á¹¢auá¹ al-Lugawiy wa al-AdÄâ€™iy - Muflihah Muflihah; M. Bashori (Jurnal Alsinatuna, 2018)
Language is essentially sound. In using Arabic, the sound spoken is related to a certain meaning. A person who has a certain language can recognize the sounds that are coupled, so that they are meaningful speeches. In this case, phonology is a branch of language that talks about the sound of language that is able to distinguish the meaning of a word. The problem that was first encountered by someone in learning oral languages, especially foreign languages ​​and regional languages, was the problem of his speech. Before learning the meaning of various words and the grammar to be faced, first he must recognize the sounds used in them. Sound science as a classical science that has received tremendous attention from the Arabs since its inception. It can be seen from what was done by the lugho scholars including Imam Jahidz. He discussed in detail about Arabic phonetics, the sound of the language, the place where the language came out and its characteristics. Thus, the researcher wanted to discuss the above matters mainly about language sounds according to Jahidz, using qualitative descriptive research methods. The result of this study is al-Jahiz’s thought that sound comes from vibration of human body using lips in oral activity, then there is a transition around the lips which moves to the ears and brain, and finally the vibration is called as vocal. It is divided into psychology and physiology.